Encapsulation of Lacto‐N‐biose based on ovalbumin and carboxymethyl cellulose microparticles: fabrication, characterisation and thermal stability. (26th March 2023) - Huang, Xin; Sun, Yue; Li, Suhong; Kitaoka, Motomitsu; Li, Tuoping
Summary: To improve the thermal stability Lacto‐N‐biose (LNB), it was encapsulated by the OVA‐CMC microparticles system. When the mass ratio of OVA:CMC:LNB was 1.5:1:1, the particle size of microparticles was 623 ± 4 nm, and the encapsulation efficiency and loading efficiency of 83 ± 1.38% and 45 ± 0.92% respectively. Analysis with the scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FT‐IR) and X‐ray diffraction (XRD) revealed that the OVA‐CMC‐LNB microparticles were spherical and uniformly distributed. The hydrogen bonding and electrostatic interactions were the main forces to assemble the microparticles. The results of the thermogravimetric analysis showed that the structure of microparticles remained stable at 240 °C. The residual amount of LNB in microparticles reached 94.3 ± 1.03% and 78.8 ± 2.38% after being heated at 90 °C for 10 and 30 min, and the thermal stability was greatly improved. In vitro simulated digestion experiments showed that the release rate of LNB in microparticles reached 95 ± 1.31%. These results provided a theoretical and technological approach for the construction of LNB delivery system improved thermal stability. Abstract : The Formation of OVA‐CMC‐LNB microparticles.